2007
DOI: 10.1073/pnas.0705683104
|View full text |Cite
|
Sign up to set email alerts
|

Processing and classification of chemical data inspired by insect olfaction

Abstract: The chemical sense of insects has evolved to encode and classify odorants. Thus, the neural circuits in their olfactory system are likely to implement an efficient method for coding, processing, and classifying chemical information. Here, we describe a computational method to process molecular representations and classify molecules. The three-step approach mimics neurocomputational principles observed in olfactory systems. In the first step, the original stimulus space is sampled by ''virtual receptors,'' whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 49 publications
2
88
1
2
Order By: Relevance
“…We recently found that interglomerular interactions increase when more odors are mixed (Silbering and Galizia, 2007). The lack of narrowing effects in the present study might therefore be related to the stimulation with monomolecular odors, which activate fewer glomeruli altogether and thus might require less interglomerular inhibition for efficient coding (Schmuker and Schneider, 2007). Alternatively, our finding might reflect a genuine difference between flies and bees, since response-narrowing occurs even with monomolecular odors in bees (Sachse and Galizia, 2003).…”
Section: Discussioncontrasting
confidence: 50%
“…We recently found that interglomerular interactions increase when more odors are mixed (Silbering and Galizia, 2007). The lack of narrowing effects in the present study might therefore be related to the stimulation with monomolecular odors, which activate fewer glomeruli altogether and thus might require less interglomerular inhibition for efficient coding (Schmuker and Schneider, 2007). Alternatively, our finding might reflect a genuine difference between flies and bees, since response-narrowing occurs even with monomolecular odors in bees (Sachse and Galizia, 2003).…”
Section: Discussioncontrasting
confidence: 50%
“…The adapted connectivity can then not be given explicitly in terms of the input correlations SS t . Rather than determining the adapted connectivity by a numerical optimization procedure we investigate the performance of the connectivity (27) and how it is affected by the rectifying nonlinearity.…”
Section: Network With Recurrent Inhibitionmentioning
confidence: 99%
“…This so-called lateral inhibition reduces input correlation and thereby improves classification performance [33], [36]. In the association layer there are two excitatory association neuron (ANe) populations that receive input from the projection neurons via plastic synapses.…”
Section: Spiking Neural Networkmentioning
confidence: 99%
“…functional groups of neurons that exist in the insect olfactory system [36]. Each glomerulus consists of a population of 6 excitatory projection neurons (PN) and a population of 6 local inhibitory neurons (LN).…”
Section: Spiking Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation